Behavior of pre-cast U-Shaped Composite Beam integrating cold-formed steel with ferro-cement slab. (May 2016) - Alhajri, T.M.; Tahir, M. M; Azimi, M.; Mirza, J.; Lawan, M.M.; Alenezi, K.K.; Ragaee, M.B.
Abstract: This paper presents experimental tests carried out to examine the structural behavior of a pre-cast U-Shaped Composite Beam by integrating cold-formed steel (CFS) with a ferro-cement slab. Nine pre-cast composite beam specimens were tested, in which the lipped channel sections were used to act compositely with the ferro-cement slabs, by means of a bolted type shear connector. A system called Precast U-Shaped Composite Beam is proposed and designed to provide composite action between the CFS sections in the tension zone and ferro-cement slab decking in the compression zone. Parametric studies were performed to investigate a number of wire mesh variations used in ferro-cement slab and thickness of the steel section. The results showed that increasing the number of wire mesh layers as well as the thickness of steel increased the ultimate load carrying capacity of composite section by up to 219%. It also reduced the formation of cracks. Finite element results proved that predicted values of strength capacity of all specimens were in close agreement with experimental values. Highlights: Structural behavior of composite beam with cold-formed steel (CFS) and ferro-cement slab. Investigation of wire mesh numbers in ferro-cement slab and thickness of CFS. Higher ultimate load capacity of beam with higher wire mesh layers and CFS thickness.